Adsorption behavior of 17 alpha-ethynylestradiol onto soils followed by fluorescence spectral deconvolution - Lima, D. L. D.
In this study, a simple and rapid procedure for monitoring adsorption of 17 alpha-ethynylestradiol (EE2) onto soil samples was developed. The used method is based on a multiwavelength fluorescence spectral deconvolution (FSD) where the emission fluorescence spectrum of a sample is considered as a linear combination of emission spectra, named reference spectra. The combination of the reference spectra allows the restitution of the shape of the emission spectrum of any unknown sample. This approach was applied to follow EE2 adsorption onto four soil samples and is an easy and low cost alternative. Adsorption experimental data showed a good fit with the Hill equation, mathematically equivalent to the Langmuir-Freundlich model assuming that the adsorption is a cooperative process influenced by adsorbate-adsorbate interactions. Molecular modelling studies clearly support the "co-operative adsorption" model, showing that after the adsorption of the first layer of EE2 molecules onto the soil, at least one more layer of EE2 is adsorbed, due to interactions established with the first adsorbed layer. Notwithstanding, packing a third row would imply interactions between two EE2 molecules that differ from the ones verified in the lowest energy structure, which also explains the plateau achieved in the adsorption curve. (C) 2011 Elsevier Ltd. All rights reserved.